Conocimiento en técnica de cepillado e higiene bucal en padres de familia del IPRESS I-3 Tupac Amaru - Maldonado Vásquez, Fernanda (2024)
KNOWLEDGE IN BRUSHING TECHNIQUE AND ORAL HYGIENE IN PARENTS OF THE IPRESS I-3 TÚPAC AMARU OBJECTIVE: This study sought to establish the relationship between the level of knowledge in brushing technique with the level of knowledge in oral hygiene of the parents of the IPRESS I-3 “Túpac Amaru”; in the year 2024. METHOD: A relationship-centered approach was followed and a non-experimental, cross-sectional, field research design was implemented with a focus on classification. A full sample of 222 participants was chosen to conduct the analysis. The methodology used involved observation, using two questionnaires as a data collection tool. RESULTS: It was found that parents' knowledge of brushing technique had the highest prevalence in the regular level 68% and there was an important percentage in the good level 22.59%. In oral hygiene knowledge, the prevalence was centered on the regular level 59.5%, and the good level reached 29.7%. Spearman's coefficients were applied to examine the relationship between the variables related to the use of questionnaires on brushing technique knowledge and oral hygiene knowledge in parents. Since the p value turned out to be less than 0.01 (p < 0.01). CONCLUSIONS: In this study it was concluded that there is a highly significant and positive relationship between brushing technique knowledge and knowledge in oral hygiene in parents of IPRESS I-3 Túpac Amaru.